Museums and Communication in the 21st Century: The Portuguese Case - Magalhães, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Bearing in mind the importance of communication for the museum, in our text we take a journey through museums from their foundation to the present day, and the relationship they have with the communication, both on the global stage and in the local Portuguese context. Since the eighteenth century, museums have emerged with the central function of communicating ideas, political ideas about communities and their respective social and cultural organizations. This trip ends with the challenges posed to today's museums from the point of view of the use of new means of communication such as the Internet or Smartphones. What are the communicative strategies of museums in an increasingly technological world? Will the use of these new means of communication, such as the Internet, eliminate physical visits to museums? Will virtual museums replace physical spaces? These will be the questions that we propose to answer in this text, using the Portuguese national museum framework as an example.